Risk factors and secondary care utilisation in a primary care population with non-tuberculous mycobacterial disease in the UK - Axson, Eleanor L. (Eur J Clin Microbiol Infect Dis, 2018)
Prior research has identified risk factors associated with developing non-tuberculous mycobacterial disease (NTMD); we identified risk factors and secondary care utilisation of NTMD patients in the UK. This was a matched case-control study using electronic healthcare records from Clinical Practice Research Datalink from 2006 to 2016. NTMD was defined using prescription data and Read codes, based on international guidelines. Risk factors for NTMD were investigated using conditional logistic regression within a representative general population. All-cause secondary care utilisation (combined inpatient, outpatient, emergency visits) was investigated for participants with linked Hospital Episode Statistics (HES), using incidence rate ratio (IRR) from 2007 to 2015. We identified 1225 individuals with NTMD. A subset of individuals (426 patients) were eligible for linkage with HES. In the adjusted model, risk factors most strongly associated with an increased likelihood of NTMD included previous tuberculosis (OR 69.0; 47.7–99.8); bronchiectasis (OR 23.3; 12.4–43.9); lung cancer (OR 14.9; 3.98–55.7); oral corticosteroids (OCS; OR 7.28; 4.94–10.7); immunosuppressive (excluding corticosteroids) medication (OR 3.05; 1.15–8.10); being underweight (odds ratio (OR) 2.92; 95% CI 1.95, 4.36); and rheumatoid arthritis (OR 2.12; 1.05–4.27). NTMD patients had significantly higher rates of all-cause secondary care utilisation than non-NTMD patients (IRR 5.80; 5.14–6.46). Using a representative adult population, we identified prior TB, bronchiectasis, lung cancer, immunosuppressive medication, and OCS as the risk factors associated with the highest odds of developing NTMD in the UK. Patients with NTMD experienced nearly six times more all-cause secondary care events following their NTMD diagnosis than patients without NTMD.